Diseño de una solución inalámbrica y cableado estructurado para el IDE Business School - Acuña García, Stefany Alejandra (2016)
With the need to share resources and exchange information networks are born in the 60s, but for such communication a set of elements needed to interconnect the computers on the network, the wiring structure, with which facilitates networking, administration and network management. Another solution for interconnecting computers within a network is wireless or wireless networks, where it is used in cases that cannot be deployed wiring (difficult access to the site) or is face the implementation of the cable. Currently many intelligent buildings, offices, academic campus, etc., have structured cabling standardized and efficient wireless network, enabling to reduce costs, share information and resources. IDE Business School is a business school founded in 1992 is located in the city of Quito, in the school problems wireless coverage present, also has no scalability in the wired part of the network, currently therefore it has an inefficient network It does not cover the expectations of students and administrative staff, therefore this project focuses on analyzing the campus infrastructure and thus design structured with due standard cabling, design the structure of the wireless network that allow provide optimal service to students and administrative staff, analyze and present the appropriate equipment the network design and both wired and wirelessly to complete the calculation of the bandwidth of the various areas of the campus.